Singapore as A Norm Entrepreneur in Strengthening Regional Cybersecurity through the Development of ASEAN CERT - Ismail Anshari, Muhammad (Department of International Relations, Hasanuddin University, 2026)
This article examines the development of ASEAN Computer Emergency Response Team (ASEAN CERT), which has experienced significant progress influenced by Singapore’s role as both an initiator and a technical norm entrepreneur in regional cybersecurity. Singapore’s active role is closely tied to its domestic interests in cybersecurity and its relevance to the progress of digital transformation, which remains vulnerable to cyber threats. Although ASEAN CERT has been adopted by consensus among all ASEAN member states, its implementation faces challenges due to differing understandings of the importance of CERT, as well as gaps in cybersecurity capacity and capability among ASEAN countries, which may hinder its implementation. This study aims to explore Singapore’s strategic position in utilizing its resources to bridge the technical CERT gap through the ASEAN cooperation framework, as well as to explore the potential of ASEAN CERT in supporting the development of ASEAN countries’ technical capacity and contributing to existing international norms.